Implementation of Project Based Learning Based Local Wisdom to Enhance Students’ Critical Thinking in Higher Education - Herlini Puspika Sari; Aldeva Ilhami; Shahid Rasool (Journal of Contemporary Islamic Education, 2025)
Islamic Religious Education (IRE) contributes to the realization of quality education in line with the Sustainable Development Goals. Optimizing the learning of prospective IRE teachers is crucial in producing superior human resources to create inclusive characters in the 21st century. This study aims to analyze the implementation of Project-Based Learning (PjBL) based on local wisdom on the critical thinking abilities of prospective IRE teachers. A triangulation mixed-method research design was used with the integration of quantitative and qualitative data to obtain comprehensive research results. The research subjects were students of the IRE study program at UIN Sultan Syarif Kasim Riau. Data collection was carried out through critical thinking ability tests and interviews of students' learning experiences. Data analysis techniques used descriptive and inferential statistical methods with the help of SPSS software to analyze quantitative data. Qualitative data analysis used the interactive model of Miles and Huberman, consisting of data collection, data reduction, data presentation, and conclusion drawing. The results showed a significant difference in the average critical thinking abilities of students between the experimental and control classes (p<0.00). The application of PjBL-based local wisdom in Islamic religious learning can improve students' critical thinking abilities. The integration of Riau Malay local culture in learning shows a positive response and becomes a learning innovation for prospective IRE teachers.